2023
DOI: 10.1186/s12916-023-02733-w
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association of remnant cholesterol with joint arteriosclerosis and atherosclerosis progression beyond LDL cholesterol

Abstract: Background Arteriosclerosis and atherosclerosis are closely related with cardiovascular disease (CVD) risk. Remnant cholesterol (RC) could predict CVD. However, its effect on joint arteriosclerosis and atherosclerosis progression remains unclear. This study aims to evaluate the association of RC with joint arteriosclerosis and atherosclerosis progression trajectories in the general population. Methods This study collected data across five biennial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Previous studies have consistently reported that PWV is closely influenced by major risk factors for CV events, including abnormal lipid phenotype, insulin resistance, and blood pressure. Our study also showed that patients with high PWV had more traditional CV risk factors and comorbidities than those with low PWV ( 26 , 34 , 35 ). Second, arterial stiffness is associated with endothelial dysfunction, platelet activation, and plaque vulnerability; the latter are significantly associated with the development and prognosis of CAD ( 36 , 37 ).…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have consistently reported that PWV is closely influenced by major risk factors for CV events, including abnormal lipid phenotype, insulin resistance, and blood pressure. Our study also showed that patients with high PWV had more traditional CV risk factors and comorbidities than those with low PWV ( 26 , 34 , 35 ). Second, arterial stiffness is associated with endothelial dysfunction, platelet activation, and plaque vulnerability; the latter are significantly associated with the development and prognosis of CAD ( 36 , 37 ).…”
Section: Discussionsupporting
confidence: 65%
“…Based on the research results, it can be concluded that: dyslipidemia is a predictor of KKM in AMI patients during hospital treatment (Aswania and Yasmin, 2020) . Wu et al , (2023), This longitudinal study shows that RC is an early risk factor for the development of joint arteriosclerosis and atherosclerosis independent of LDL-C in the general population, providing new evidence of the need for RC monitoring to improve cardiovascular health. RC may serve as a target for the prevention and intervention of arteriosclerosis and atherosclerosis, even in people with optimal LDL-C levels (Wu et al , 2023) .…”
Section: Discussionmentioning
confidence: 69%
“…Ji et al [ 70 ] also found that baPWV was correlated with WHR and visceral fat area, but not with BMI and waist circumference in eastern Asian populations. Remnant cholesterol was independently associated with joint arteriosclerosis and atherosclerosis progression measured by baPWV beyond LDL-C [ 71 ]. As body fat is closely related with lipids, we hold opinion that lipids had the potential mediating effects at the relationship between waist-related indices and baPWV.…”
Section: Discussionmentioning
confidence: 99%